RETRACTED: STAT3 Promotes Invasion and Aerobic Glycolysis of Human Oral Squamous Cell Carcinoma via Inhibiting FoxO1 - Zheng, Min; Cao, Ming-xin; Yu, Xiang-hua; Li, Li; Wang, Ke; Wang, Sha-sha; Wang, Hao-fan; Tang, Ya-Jie; Tang, Ya-ling; Liang, Xin-hua (Frontiers in Oncology, 2019)
Signal transducer and activator of transcription 3 (STAT3), a previously accepted tumor-promoting protein in various malignancies, plays a key role in the process of cancer glycolysis. However, the role and potential mechanism of STAT3 in aerobic glycolysis and progression of oral squamous cell carcinoma (OSCC) has not been explored. In the present study, we demonstrated that STAT3 knockdown remarkably inhibited migration, invasion, expressions of epithelial-mesenchymal transition (EMT) markers, and aerobic glycolysis of OSCC cells by up-regulation of FoxO1. Consistently, the expression of nuclear Tyr705-phosphorylated STAT3, an active form of STAT3, was significantly elevated in OSCC tissues compared with adjacent normal tissues, and increased nuclear staining of Tyr705-phosphorylated STAT3 was associated with metastasis and shorter overall survival. Moreover, FoxO1, which was also mainly expressed in OSCC specimens, decreased in poorly-differentiated tissues compared with the relatively well-differentiated ones, and inversely correlated with the expression of nuclear Tyr705-phosphorylated STAT3 from patients with OSCC. Hence, our findings collectively characterized the contributing role of STAT3/FoxO1 in invasion and aerobic glycolysis of OSCC cells, which may lead to the worse clinical outcome.